2021
DOI: 10.1002/int.22575
|View full text |Cite
|
Sign up to set email alerts
|

Improving the emotion‐based classification by exploiting the fuzzy entropy in FCM clustering

Abstract: Emotion detection in the natural language text has drawn the attention of several scientific communities as well as commercial/marketing companies: analyzing human feelings expressed in the opinions and feedback of web users helps understand general moods and support market strategies for product advertising and market predictions. This paper proposes a framework for emotion‐based classification from social streams, such as Twitter, according to Plutchik's wheel of emotions. An entropy‐based weighted version o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“… Clustering text [46]: These algorithms are a type of unsupervised learning algorithms that are used in SA to group similar text samples together based on their sentiment. Clustering algorithms can be useful for tasks such as discovering latent themes/topics [15] within a dataset of text or grouping similar text samples together for further analysis. In line with the above concepts, [9] use Latent Dirichlet Allocation (LDA) and K-means to extract themes among the topics dis-cussed on Twitter/X posts in relation to natural disaster.…”
Section: A the Most Employed Clustering Algorithms Their Benefits And...mentioning
confidence: 99%
See 2 more Smart Citations
“… Clustering text [46]: These algorithms are a type of unsupervised learning algorithms that are used in SA to group similar text samples together based on their sentiment. Clustering algorithms can be useful for tasks such as discovering latent themes/topics [15] within a dataset of text or grouping similar text samples together for further analysis. In line with the above concepts, [9] use Latent Dirichlet Allocation (LDA) and K-means to extract themes among the topics dis-cussed on Twitter/X posts in relation to natural disaster.…”
Section: A the Most Employed Clustering Algorithms Their Benefits And...mentioning
confidence: 99%
“…In the light of the above, LDA is a generative probabilistic model of a corpus [54] used as a topic modeling algorithm that can discover the underlying themes in a collection of documents. LDA can automatically identify latent topics [15] in a set of reviews and offer a method to comprehend how various sentiments are distributed across a dataset.…”
Section: ) Topic Modeling Techniques In Nlpmentioning
confidence: 99%
See 1 more Smart Citation
“…The source domain incorporates data with multiple distribution characteristics. The feature classification [25][26][27] of the source domain data is the beginning of constructing different horizons. However, in this process, we do not need to assign corresponding labels to each type of data, but only need to group data with similar or the same characteristics into one category.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…An extension of the Fuzzy C-means (FCM) partitive clustering algorithm is applied to classify documents where the term frequency inverse document frequency measure (TF-IDF) is used to assess the relevance of emotion categories in the document. A variation of this framework is used in [12] to classify document extracts from tweets; the authors applied an entropy variation of FCM to classify documents using the primary and secondary pleasant and unpleasant Plutchik emotion categories and they showed that their approach improves the classification accuracy of the emotion classification framework [11]. In [13], a new emotion classification framework called FREDoC is proposed; it is based on a fuzzy-based emotion classification model applied instead of the FCM clustering algorithm to classify documents considering the primary and secondary Plutchik emotion categories.…”
Section: Introductionmentioning
confidence: 99%